Distinções entre modalidade deôntica objetiva e subjetiva no português falado: o caso do verbo 'dever' - Gasparini-Bastos, Sandra Denise [UNESP] (2014)
The modal distinctions proposed by Hengeveld (2004), reexamined by Hengeveld and Mackenzie (2008) within the Functional Discourse Grammar (FDG), consider the existence of five types of modality: facultative, deontic, volitive, epistemic and evidential. Taking into special account the deontic modality, there are evidences that it can be subdivided into objective and subjective, as analyzed by Olbertz and Gasparini-Bastos (2013) in auxiliary constructions of spoken Spanish. This wok aims to investigate the contextual elements that favor the interpretation of these two values when they are expressed by the modal auxiliary verb “dever” (must) in spoken Portuguese data.